Muakhi as a Relational Resource in House-of-Worship Disputes: Anjau Silau and FKUB Mediation in Bandar Lampung - Zarkasi, Ahmad; Salim, Luthfi; Rosana, Ellya (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Disputes over houses of worship in Indonesia are often treated as regulatory problems, although their development also reflects unequal majority–minority relations, contested building use, local opposition, and limited communication. This article examines how muakhi, a Lampung conception of brotherhood or socially constituted kinship, was interpreted and translated into anjau silau, a relational practice of visiting and dialogue, in the GKKD and GPIN disputes in Bandar Lampung. It also examines how the Forum for Religious Harmony (FKUB) connected these culturally grounded practices with formal mediation. The study employed a qualitative multiple-case design based on interviews with 11 purposively selected informants and relevant case documents. Within-case and cross-case thematic analyses were used to compare the disputes’ trajectories, cultural interpretations, communication practices, mediation processes, and immediate arrangements. The findings show that participants associated muakhi with brotherhood, mutual recognition, visiting, listening, and deliberation rather than with a single formal customary procedure. Its most observable enactment in the two cases was anjau silau. However, the documented visits occurred primarily after tensions had emerged and were perceived as helping reopen communication and limit further escalation rather than preventing the original disputes. FKUB connected these relational practices with multiparty meetings and administrative negotiations. Mediation produced a temporary worship arrangement in the GPIN case, whereas the available evidence does not establish a conclusive settlement in the GKKD case. The findings suggest that muakhi can provide a culturally intelligible relational resource for mediation when its application remains inclusive, consistent with religious rights, and connected to transparent institutional procedures.